Interferências psicológicas no cenário esportivo: implicações em treinadores - Carvalho, Jean Bastos de [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The sports context is composed of several factors that must be developed in the best possible way, being balanced so that the results provided by the sports actions are the most adequate. In this way, it is essential to work on psychological aspects that are often left out. An important point that should be emphasized is the ability of a coach to influence his athletes, also needing a psychological balance to deal with adversity and clearly pass to the team what he expects, seeking not to unbalance his athletes and generate damages to the athlete performance and may alter behavior and cause disturbances in athletes. Therefore, it is important to understand the psychological aspects that can influence the career of a sports coach. Thus, the purpose of this study is to analyze how psychological interferences can affect coaches at different times in their careers. The method used in this research was based on bibliographical and documentary review. In this way, it was possible to verify that the sports coaches can suffer diverse external interferences that cause in emotional alterations and, consequently, damages in aspects like decision making, results, influence and leadership in the team. Therefore, we note the importance of the work done by the sports psychologist, along with the technical committee, coaches and athletes, because it is not enough to base research on athletes, but also on their leaders, since coaches can directly influence athletes. Thus, we were able to better understand the psychological factors influencing the career of sports coaches, a rare fact in the literature, since we generally only study athletes' opinions about certain situations. In addition, it is also expected that the present research has contributed in the awakening of interest to new researchers on studies involving coaches, since they are essential figures in the context of the sport

O contexto esportivo é composto por diversos fatores que devem ser desenvolvidos da melhor maneira possível, estando equilibrados para que os resultados proporcionados pelas ações esportivas sejam os mais adequados. Desta forma, é essencial trabalharmos aspectos psicológicos que, muitas vezes, são deixados de lado. Um ponto importante a ser ressaltado é a capacidade que um treinador possui de influenciar seus atletas, também necessitando de equilíbrio psicológico para saber lidar com adversidades e passar com clareza à equipe aquilo que espera da mesma, buscando não desequilibrar seus atletas e gerar danos à performance, podendo alterar comportamentos e causar distúrbios nos esportistas. Por isso, é importante entendermos os aspectos psicológicos que podem influenciar a carreira de um treinador esportivo. Assim, o objetivo deste estudo é analisar como as interferências psicológicas podem afetar os treinadores em diversos momentos de suas carreiras. O método utilizado neste trabalho foi baseado na pesquisa de caráter de revisão bibliográfica e documental. Desta maneira, foi possível constatar que os treinadores esportivos podem sofrer diversas interferências externas que acarretam em alterações emocionais e, consequentemente, danos em aspectos como tomada de decisão, resultados, influência e liderança na equipe. Portanto, nota-se a importância do trabalho realizado pelo psicólogo do esporte juntamente à comissão técnica, treinadores e atletas, pois não basta apenas basearmos as pesquisas nos esportistas, mas também em seus líderes, pois os técnicos podem influenciar diretamente diversos aspectos da carreira dos atletas. Assim, pudemos compreender melhor os fatores psicológicos influentes na carreira dos treinadores esportivos, fato raro na literatura, pois geralmente estuda-se apenas a opinião dos atletas sobre determinadas situações. Além disso, também espera-se que a presente pesquisa tenha...
Psychological interferences in the sportive scenario: implications in trainers
Keywords: Esportes - Aspectos psicológicos; Treinadores de atletas; Atletas